Exocentric compounds in Akan. (October 2017) - Appah, Clement K. I.
Abstract : The purpose of this paper is to investigate exocentric compounds in Akan and to present a Construction Morphology account of their properties. I show that the complex issue of exocentricity is better accounted for if we distinguish between formal and semantic exocentricity. I present Bauer's (2008, 2010) typology of exocentric compounds ( bahuvrihi, exocentric synthetic, transpositional exocentric, exocentric co-compounds and metaphorical exocentric compounds ) and test the Akan data against them, showing that all Akan compound types (N-A, N-N, N-V, V-N, and V-V) are either exocentric or have exocentric subtypes which fall into three of the five types identified by Bauer. They are bahuvrihi compounds and exocentric synthetic compounds (of which I identify two subtypes each) and transpositional exocentric compounds . I present the properties of each identified type of Akan exocentric compound using formalisms from Construction Morphology (Booij 2010b ) in which compounds are word-level constructions capable of having holistic properties. The unexpressed features of the exocentric compounds are regarded as holistic constructional properties that do not emanate from the constituents per se.